Oxygen desaturation during sleep and exercise in patients with interstitial lung disease. Issue 5 (May 1987) - Midgren, B; Hansson, L; Eriksson, L; Airikkala, P; Elmqvist, D
Abstract : The relations between mean and maximum fall in arterial oxygen saturation (SaO2) during sleep, hypoxaemia during moderate and maximum exercise, and lung mechanics were studied in 16 patients with interstitial lung disease. Mean and minimum SaO2 during sleep were significantly related to each other and to daytime oxygenation but not to lung mechanics. Although the maximum fall in SaO2 during sleep was similar to the fall during maximum exercise (a level seldom achieved during normal daily activities), profound hypoxaemic episodes during sleep were rare and brief and therefore contributed little to the mean SaO2. The fall in mean SaO2 during sleep was not significant and was considerably less than during moderate exercise (average 0.5 v an estimated 4.5%, p less than 0.05). It is therefore concluded that in patients with interstitial lung disease oxygen desaturation during sleep is mild and less severe than hypoxaemia during exercise.